ANALISIS MOTIVASI BELAJAR SISWA KELAS III TERHADAP PENGGUNAAN TEKNOLOGI LCD PROYEKTOR DI SEKOLAH DASAR NEGERI SENDANGMULYO 02 SEMARANG - Ahmad Malik Pujiono Ahmad; Henry Januar Saputra; Husni Wakhyudin; Rafika Nuriafuri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to analyse the learning motivation of third grade students in the context of using LCD projector technology at Sendangmulyo 02 Semarang primary school. The use of this technology has a positive impact on students' learning motivation, improves the quality of learning, and facilitates better understanding of concepts. This study was conducted by observing 28 third grade students at Sendangmulyo 02 Semarang primary school. The instrument used was a questionnaire to measure students' learning motivation level to see students' interaction with LCD projector technology during the learning process. The results showed that students showed high interest in the use of this technology, felt more involved and enthusiastic in understanding the material when LCD projector technology was used. Factors such as the availability of adequate technology infrastructure, the quality of learning materials presented through projectors, and teachers' ability to integrate technology affect students' learning motivation. It is recommended that schools increase the use of LCD projector technology, train teachers in its use, and provide adequate technology infrastructure to improve students' learning experience and their learning motivation..